1998
DOI: 10.1128/jvi.72.12.9514-9525.1998
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Repeated Adenovirus-Mediated Gene Transfer in Mice Lacking both Tumor Necrosis Factor Alpha and Lymphotoxin α

Abstract: The efficiency of adenovirus-mediated gene transfer is now well established. However, the cellular and the humoral immune responses triggered by vector injection lead to the rapid elimination of the transduced cells and preclude any efficient readministration. The present investigation focuses on the role of tumor necrosis factor alpha (TNF-α), a proinflammatory cytokine, and the related cytokine lymphotoxin α (LTα), in mounting an immune reaction against recombinant adenovirus vectors. After gene transfer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Although coagulation FX and natural IgM are the principal blood factors that bind to HAdv in the blood after intravenous virus administration to nonimmune hosts, these factors do not protect the virus from neutralization by HAdv-specific neutralizing antibodies in HAdv-C5 immune hosts. Indeed, liver-directed gene transfer was abrogated upon administering HAdv vector, based on the same serotype that was used for immunization of animals prior to analyzing liver-directed gene delivery [22][23][24]. Intravenous administration of HAdv to hosts with virus-specific immunity leads to the formation of HAdv-antibody (Ab) immune complexes that are sequestered by FcR-positive cells including dendritic cells (DCs), neutrophils [25], and tissue-resident macrophages.…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
“…Although coagulation FX and natural IgM are the principal blood factors that bind to HAdv in the blood after intravenous virus administration to nonimmune hosts, these factors do not protect the virus from neutralization by HAdv-specific neutralizing antibodies in HAdv-C5 immune hosts. Indeed, liver-directed gene transfer was abrogated upon administering HAdv vector, based on the same serotype that was used for immunization of animals prior to analyzing liver-directed gene delivery [22][23][24]. Intravenous administration of HAdv to hosts with virus-specific immunity leads to the formation of HAdv-antibody (Ab) immune complexes that are sequestered by FcR-positive cells including dendritic cells (DCs), neutrophils [25], and tissue-resident macrophages.…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
“…Although much of clinical HIV-associated risk of infection in the Western world could be understood under this paradigm, this dichotomy of T-cell subsets was incomplete. This particularly became evident as prophylaxis against the opportunistic pathogen Pneumocystis became widespread in the late 80's to the early 90's and bacterial pneumonia increased as a major a pulmonary complication of AIDS [11] [12]. Just like infections ascribed to Th1 or Th2 immunity, epidemiological data also suggested that lung infections with extracellular bacteria were also inversely associated with CD4+ T-cells in peripheral blood [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Presentation of exogenous viral antigens by MHC class II molecules has been suggested to induce the Th1 subset of CD4 + T cells that strengthen the cytotoxic response, as well as the Th2 subset of CD4 + T cells involved in mounting an efficient humoral response by producing tumor necrosis factor alpha (TNF-α) and/or lymphotoxin α (LT α). 18) The B-cell response to an Ad infection consists essentially of IgG antibodies. Since some of these antibodies are neutralizing, efficient redosing is prevented.…”
mentioning
confidence: 99%